Antimicrobial resistance of commensal Escherichia coli and Enterococcus faecalis isolated from clinically healthy captive wild animals in Seoul zoo - Kim, Minsu; Kim, Myeongsu; Yeo, Yong-Gu; Lee, Young-Tae; Han, Jae-Ik (Frontiers in Veterinary Science, 2024)
Despite the importance of antimicrobial resistance, only a few studies on the antimicrobial susceptibility on wild animals have been conducted owing to their population, accessibility, and characteristics. The objective of this study was to investigate the prevalence and characteristics of antimicrobial resistance pattern in Escherichia coli and Enterococcus faecalis isolated from the feces of captive wild animals in a zoo. A total of 61 captive wild animals were included in this study. E. coli was isolated from 58 of the 61 animals and E. faecalis was isolated from 29 animals. Among the isolated E. coli strains, ampicillin exhibited the highest resistance rate (27/29, 93.1%). Of these, 18 strains (18/29, 62%) showed multidrug resistance. The multilocus sequence typing (MLST) test showed that only ST155 was detected twice, while the other 16 strains showed different ST types. Among the E. faecalis strains, two were susceptible to all tested antimicrobials, whereas the remaining 27 strains showed resistance to one or more antimicrobials. Nine strains (9/27, 31%) showed multidrug resistance. Among the E. faecalis strains, resistance to quinupristin/dalfopristin was the highest at 96.3% (26/27), while the MLST of the nine MDR strains showed no predominant ST. Genetic association with human isolates or livestock products was observed in the isolated ST types. This indicates that antibiotic resistance in the zoo is responsible for the use of antibiotics and the partial horizontal transmission between humans and animals through feeding or contact.